A journey with Fred Hoyle - Wickramasinghe, Chandra, 1939- (World Scientific, 2013)
This is the story of the author's unique scientific journey with one of the most remarkable men of 20th century science. The journey begins in Sri Lanka, the author's native country, with his childhood acquaintance with Fred Hoyle's writings. The action then moves to Cambridge, where the famous Hoyle-Wickramasinghe collaborations begin. A research programme which was started in 1962 on the carbonaceous nature of interstellar dust leads, over the next two decades, to developments that are continued in both Cambridge and Cardiff. These developments prompt Hoyle and the author to postulate the or.